Wildflowers of the Indiana Dunes National Park - Pilla, Nathanael; Namestnik, Scott (Book collections on Project MUSE., 2022)
"Indiana Dunes, located on the picturesque coast of Lake Michigan, is one of the most biologically diverse parks in the US national park system. Keen hikers can spot white mayapple blooms, orange-fringed orchids, pink lady slippers, and more. Wildflowers of the Indiana Dunes National Park offers visitors a unique handbook highlighting over 160 of the common and exceptional wildflowers found along the trails of Indiana Dunes National Park and the surrounding area. This accessible field guide bypasses the dry nature of many wildflower guides. In addition to the usual scientific species names, descriptions, and bloom periods, Nathanael Pilla and Scott Namestnik offer deeper narratives-folklore surrounding the flowers, look-alikes, animals associated with the plants-that will be remembered much more easily than the length of a petal. Illustrated with over 350 color photographs, Wildflowers of the Indiana Dunes National Park will be an asset to the casual hiker of Indiana Dunes National Park, a useful tool to the experienced botanist, and a delight to anyone interested in wildflowers"--